Preparation and Characterisation of Zinc-Aluminium Eutectic Alloy - Ayasamy, Priya Tharshini; NUR AZAM BIN BADARULZAMAN (Research Progress in Mechanical and Manufacturing Engineering, 2025)
This study investigates the preparation, characterization, and mechanical properties of zinc-aluminium (Zn-Al) alloys, focusing on impact toughness, hardness, and microstructural characteristics. The alloys were fabricated using sand casting and their microstructures were examined using scanning electron microscopy (SEM) and energy dispersive spectroscopy (EDS). The microstructural investigation revealed unique grain shapes and phase distributions, with the eutectic alloy displaying lamellar structures and the hypereutectic alloy having dendritic patterns. The microstructural changes were associated with mechanical parameters in later tensile, hardness, and impact assessments. The tensile test showed that a hypereutectic alloy had exceptional ductility, making it suitable for flexible applications. The hypoeutectic alloy had superior yield strength and elastic modulus, making it suitable for structural applications. Pure zinc, despite having lower strength and modulus, showed enhanced ductility due to its larger grain structure. The Izod impact test showed that both Zn-Al alloys and pure zinc absorbed minimal energy, making them brittle for impact-sensitive applications. Pure aluminium showed more energy absorption, indicating enhanced durability. The research highlights the importance of alloy composition, microstructure, and casting conditions in enhancing materials for applications in sectors like automotive, aerospace, and die-casting.